Microprocessors and microcomputers hardware and software - Tocci, Ronald J. (Prentice Hall, 1997)
Using the currently popular, powerful, yet easy to understand Motorola 68HC11 microcontroller as a representative example, this text provides a comprehensive introduction to the concepts, principles, and techniques of microprocessors and microprocessor-based systems.